Bovine Tuberculosis Testing in Colombia: Comparative Histopathological, Microbiological, and Molecular Biology Findings - Cadavid, Paula Palomino; Balvin, Dubel Ignacio; Julio, Rafael Villarreal; Ramos, Enderson Murillo; Gutierrez, Jesus Berdugo; Buitrago, Jhon Didier Ruiz; Garcia, Rene Ramirez (Journal of Buffalo Science, 2024)
Introduction: Bovine tuberculosis (bTB) is a zoonotic infectious disease present in Colombia, caused by Mycobacterium bovis, and causes tuberculosis in water buffalo (Bubalus bubalis). Diagnosis of bovine tuberculosis through the intradermal test is difficult; evaluating and understanding the behavior of other diagnostic tests is necessary. Objective: To describe the behavior and results of different diagnostic methods for bovine tuberculosis in water buffalo positive for the Purifed Proteic Derivate (DPP) intradermal test. Methodology: In water buffaloes positive for comparative cervical tuberculin test, different diagnostic methods were applied, described, and compared: Ziehl-Neelsen staining, microbiological culture, histopathological analysis, and PCR-HRM. Results: Histopathological tests showed that 26 water buffalo positive for DPP (52%) had histological lesions compatible with bovine tuberculosis. 37% of the evaluated samples from tuberculin-positive Buffalo's lungs and secondary lymph nodes showed acid-alcohol-resistant bacillus with Ziehl-Neelsen staining. Four samples of Mycobacterium bovis from tuberculin-positive buffalo were isolated and identified, with two of these isolates confirmed from tissues with PCR-HRM, and three buffalo with microbiological isolates presented granulomatous lesions through histological analysis. Seventeen tuberculin-positive buffalo (34%) tested positive for real-time PCR HRM, and nine of these buffalo did not have histological lesions compatible with bTB and were confirmed with the molecular test. Conclusion: Our results provide positive evidence of histological findings, microbiological isolation, and molecular diagnosis of tuberculin-positive water buffalo in the lowlands of Colombia. None of the complementary tests performed showed 100% concordance with the comparative cervical tuberculin test results for bTB.